2015
DOI: 10.1007/s12110-015-9229-4
|View full text |Cite
|
Sign up to set email alerts
|

Testing Theories about Ethnic Markers

Abstract: In recent years, evolutionary psychologists and anthropologists have debated whether ethnic markers have evolved to solve adaptive problems related to interpersonal coordination or to interpersonal cooperation. In the present study, we add to this debate by exploring how individuals living in a modern society utilize the accents of unfamiliar individuals to make social decisions in hypothetical economic games that measure interpersonal trust, generosity, and coordination. A total of 4603 Danish participants co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 107 publications
(100 reference statements)
0
9
0
Order By: Relevance
“…A second factor is the nature of the interaction, which on purpose is kept very simple in the model of Fu and colleagues. Homophily may have a crucial role in coordinating the agents’ behaviour in a coordination game 56 57 58 or, more generally, in achieving a favourable outcome in ambiguous situations 59 60 61 . For example, most social interactions have a large number of possible (Nash) equilibrium solutions 27 28 33 .…”
Section: Discussionmentioning
confidence: 99%
“…A second factor is the nature of the interaction, which on purpose is kept very simple in the model of Fu and colleagues. Homophily may have a crucial role in coordinating the agents’ behaviour in a coordination game 56 57 58 or, more generally, in achieving a favourable outcome in ambiguous situations 59 60 61 . For example, most social interactions have a large number of possible (Nash) equilibrium solutions 27 28 33 .…”
Section: Discussionmentioning
confidence: 99%
“…One psychological explanation for positive reactions to norm-conforming ingroup members is that norm conformity promotes between-group distinctiveness, which in turn helps to maintain their social identity (Tajfel 1981). A distinct but not incompatible explanation is that norm conformity might function as "ethnic markers" that help us to identify reliable partners for the purposes of coordination and the pursuit of mutual goals (McElreath, Boyd, and Richerson 2003;Jensen et al 2015).…”
Section: Positive Social Maintenancementioning
confidence: 99%
“…Experimental simulations demonstrate that group cooperative strategies between individuals who share a group marker are able to arise and proliferate under a wide range of conditions (Hammond & Axelrod, 2006;Ihara, 2011;Riolo et al, 2001). Furthermore, results of laboratory one-shot economic games have shown that strangers who share group markers (even if arbitrarily assigned) are more likely to cooperate and act altruistically towards each other than participants who do not share a marker (Chen & Li, 2009;Hewstone, Rubin, & Willis, 2002) [for a critical discussion of some of this empirical evidence, see Jensen, Petersen, Høgh-Olesen, & Ejstrup, 2015]. An alternative account proposes that markers facilitate coordination among individuals in a heterogeneous population because they signal one's behavioural type/preferences/habits and allow unfamiliar individuals to identify others who share their social norms/cultural expectations (Gil-White, 2001;McElreath et al, 2003).…”
Section: Introduction "All People Within the Four Seas [The World] Are Brothers" -Confuciusmentioning
confidence: 99%
“…An alternative account proposes that markers facilitate coordination among individuals in a heterogeneous population because they signal one's behavioural type/preferences/habits and allow unfamiliar individuals to identify others who share their social norms/cultural expectations (Gil-White, 2001;McElreath et al, 2003). Support for this conjecture comes from field research (Barth, 1969), laboratory studies (Efferson, Lalive, & Fehr, 2008;Jensen et al, 2015) and modelling (McElreath et al, 2003).…”
Section: Introduction "All People Within the Four Seas [The World] Are Brothers" -Confuciusmentioning
confidence: 99%